Pertimbangan Hakim Dalam Menjatuhkan Putusan Yang Menyatakan Tuntutan Penuntut Umum Tidak Dapat Diterima Serta Upaya Hukumnya Dalam Perkara Penganiayaan - Valtala Leifyumna Jauza (Verstek, 2017)
Public interest is frequently impinged by someone in social life  , to evoke feel safe and justice in society, we need the existence of process to handle someone bothering the importance. The Conference Process is the last process in its solution, which product is in the form of Verdict. Sometimes Decision which released by Judge unlike what asked by Public Procecutor in its Libel.      In this case, the defendant accidentally hit Ricky with a block of wood which caused them had a fight. Ricky got injured and felt it was inappropriate so he couldn’t accept that. He immediately reported to the local police station and then do the visum . after that, the trial had been done with regular events.       The purpose of this research is to determine Judge’s legal considerations that made the Verdict states Public Procecutor’s libel is not acceptable. This research shows that case Number Nomor 103/Pid/2014/ PN Wno is misdemeanor, which means its litigation  should not be done with regular session because it is contrast with applicable laws.      Keywords: Conference, Public Prosecutor, Unacceptable Libel